Faktor pengaruh resiliensi mangsa banjir: kajian kes di Kelantan - Noremy Md. Akhir,; On, Kan Soh; Nur Hafizah Md. Akhir, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The massive flood occurred in December 2014 in Kelantan was an unexpected disaster that has affected not only on physical destruction but leaving flood victims with psychological problems. However, previous studies have concluded that resiliency is a crucial element that can protect the victims from experiencing severe psychological problems effect from disasters. Therefore, this study was conducted to explore the factors influencing resiliency of flood victims who suffered property total loss as a result of the disaster. A total of 28 flood victims were selected for in-depth interviews, five months after the floods occurred. Qualitative approach using case study as a research design is used to carry out this study. Informants were selected based on purposive sampling using inclusive criteria. Two face-to-face interview sessions were conducted to all informants separately. The data were collected within three months from May to July 2015. The collected data were transcribed and analyzed using thematic analysis. The findings reported that there are five factors influence on informants’ resilience, which include self-efficiency, coping strategies, sense of community, community leaders and social support. It was found that informants with high resiliency were able to perform self-recovery, while informants with low-resiliency are suggested to undergo for relevant intervention programs including empowerment of self-help support at individual level, building collective capacity at community level, strengthening community leaders to provide holistic social support, which as will lead to help improve the physical and psychosocial wellbeing of flood victims.